Late blight of potato and its management through the application of different fungicides and organic amendments: a review - Tiwari, Injila; Shah, Kabita Kumari; Tripathi, Subina; Modi, Bindu; Subedi, Sudeep; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Late the blight of potato is a devastating and one of the economic diseases of potato and other plants belonging to family Solanaceae. Late blight, caused by Phytophthora infestans, is one of the most threatening pathogenic diseases which not only results in direct crop losses but also cause farmers to embrace huge monetary expenses for disease control and preventive measure. It was first reported during the Irish Potato Famine, leading to massive starvation in Ireland and other parts of Europe during the middle of 19th century. Phytopthora harms the foliar portion in the field and also the tuber in the storage that can result in complete crop failure in potato. The pathogen has distinct survival mechanisms and two life cycles infection processes. The development of a sexual spore known as oospore includes two types of pairs, A1 and A2. The spores are introduced to good plants by wind and rain. Different methods for prevention of crops from late blight has been developed and used worldwide. An integrated disease management strategy includes successful control of this disease. Cultural control, chemical management, and advanced disease management are the most effective interventions. Integration of late blight control in tropical regions with abundant fungal inoculants in most months of the year was also seen as one of the best choices in disease management. This paper reviews the significance of late blight of potato and controlling strategies adopted for minimizing yield losses incurred by this disease by the application of synthetic fungicides and different organic amendments.